Perlindungan Hukum Terhadap Hak-Hak Siswa Disekolah - Syahrial Fitri (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2025)
This study aims to analyze the legal protection of students' rights in schools and identify the factors that influence the implementation of such protections. A qualitative approach was employed using a literature study method, along with an analysis of legal documents and educational policies. The findings of the study indicate that although various regulations on the protection of students' rights have been established, their implementation still faces significant challenges, such as the lack of awareness among educators regarding students' rights and the insufficient mechanisms for effective monitoring. Moreover, many students are not fully aware of their rights, making it difficult for them to lodge complaints when their rights are violated. The conclusion of this study is that strengthening the policies on students' rights protection is necessary through increased human rights education in schools and stricter monitoring of policy implementation by both schools and the government.